The Social Acceptance of Secondary School Students with Learning Disabilities (LD) - Teja Lorger; Majda Schmidt; Karin Bakračevič Vukman (Center for Educational Policy Studies Journal)
This paper aims to shed light on the level of social acceptance among students with learning disabilities (LD4) in various secondary school vocational programs in comparison with their peers without disabilities. Our findings are based on an empirical study that comprised 417 students,5 of whom 85 were students with LD. Based on sociometric analyses of all participating classes, we determined that students with LD were less integrated into the classroom in comparison to their peers without LD. The results of the sociometric analysis show statistically significant differences in the sociometric position between students with LD and students without LD. While students with LD were most frequently perceived as rejected, students without LD were seen as popular or average. In addition, students with LD see themselves as less socially self-efficient compared to their peers. The results of our study mostly refer to boys, because the sample comprised 359 boys and 58 girls. We believe that pro-inclusion teachers with appropriately developed strategies for strengthening students’ social skills, as well as positive attitudes and sufficient knowledge about the special needs of students can have a significant impact on the social acceptance of students with special needs in the classroom community.